Conducting research interviews - Rowley, Jennifer (Management research news, 2012)
Purpose - The purpose of this paper is to draw on experience in supervising new researchers and the advice of other writers, to offer novice researchers, such as those engaged in study for a thesis, a pragmatic introduction to conducting research interviews.Design methodology approach - After a brief introduction, the paper is organized into three main sections: designing and planning interviews, conducting interviews, and making sense of interview data. Within these sections, 11 questions often asked by novice researchers are posed and answered.Findings - Novice interviewers need to conduct some research interviews in order to start to develop their skills in the craft of interviewing. This paper is designed to give novice interviewers the advice and support that they need before starting on this journey.Originality value - Other research methods texts offer advice on research interviews, but their advice is not tailored specifically to new researchers engaged in research for a thesis. They tend to offer options, but provide limited guidance on making crucial decisions in interview planning, design, conduct, and data analysis.